(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The global epidemic of road traffic accidents is still increasing. The present study was aimed to assess the level of awareness regarding road safety among the study participants and to study the behaviour patterns while using motorised vehicles among the study participants. Methods: The present cross-sectional study was conducted in Saveetha medical college and hospital, Chennai. A total of 125 students were studied. The study period was from 21st January 2019 to 30th March 2019. Results: In total, 125 medical students were studied, ranging from 1st to final year M.B.B.S. of age 19-24 years; the mean age being 21.4 .Only 65(52%) participants wear helmet and only 22(17.6%) participants interpreted Gap-In-Median correctly. Conclusions: The awareness regarding road safety measures among the study group was satisfactory but interpretation of the road signs was not satisfactory -only 17.6% interpreted them correctly. The behavioural patterns among medical students are not satisfactory-only 52% of students wear helmet while riding, only 49.6% wear seat belts always while 41.6% wear seatbelt’s sometimes and 24% don’t follow lane rules while driving.